Cognitive linguistics and religious language - Richardson, Peter, (Professor of English), author.
1 online resource
Keywords: "This book comprehensively introduces cognitive linguistics and applies its tools to religious language. Drawing on authentic samples from a range of faiths, text types, and modes of interactive discourse, the authors accessibly define concepts like embodied cognition, agency, metaphor analysis, and Dynamic Systems Theory, illustrate how they are and can be used in analyzing religious language, and offer thorough pedagogical material to aid learning and application. Advanced students and scholars of linguistics, discourse analysis, cognitive science, and religious and biblical studies will benefit from this practical guide to understanding and conducting research on religious discourse"--